2021
DOI: 10.3389/fonc.2021.663406
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Silencing of Immune-Checkpoint Receptors in Bone Marrow- Infiltrating T Cells in Acute Myeloid Leukemia

Abstract: BackgroundImmune-checkpoint (IC) inhibitors have revolutionized the treatment of multiple solid tumors and defined lymphomas, but they are largely ineffective in acute myeloid leukemia (AML). The reason why especially PD1/PD-L1 blocking agents are not efficacious is not well-understood but it may be due to the contribution of different IC ligand/receptor interactions that determine the function of T cells in AML.MethodsTo analyze the interactions of IC ligands and receptors in AML, we performed a comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Recently, it was observed that bone marrow-infiltrating CD8 + T cells from acute myeloid leukemia (AML) patients demonstrated downregulated expression of immune checkpoint (IC) receptors including PD-1 which could contribute to upregulation of immune checkpoint ligands such as PD-L1 due to poor PD-1/PD-L1 interaction ( 117 ). However, treatment with VPA increased the expression of IC receptors.…”
Section: Effects Of Hdac Inhibitors On Immune Checkpoint Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was observed that bone marrow-infiltrating CD8 + T cells from acute myeloid leukemia (AML) patients demonstrated downregulated expression of immune checkpoint (IC) receptors including PD-1 which could contribute to upregulation of immune checkpoint ligands such as PD-L1 due to poor PD-1/PD-L1 interaction ( 117 ). However, treatment with VPA increased the expression of IC receptors.…”
Section: Effects Of Hdac Inhibitors On Immune Checkpoint Proteinsmentioning
confidence: 99%
“…Likewise, genetic ablation of dual-specificity phosphatase 2 (DUSP2) (a newly identified T cell suppressor and key epigenetic immune modulator acting via HDAC complex) in CD8 + T cells upregulated genes involved in IC receptors. Interestingly, both VPA and DUSP 2 knockdown improved the effector functionality of CD8 + T cells; suggesting that downregulation in IC receptors is associated with pathological HDAC expression and resistance to IC inhibitors ( 117 ). Collectively, these studies depict HDAC inhibitors demonstrate the potential to increase immune checkpoint proteins expression and promote sensitivity to ICB as a combination therapy for ICB resistance in cancer patients.…”
Section: Effects Of Hdac Inhibitors On Immune Checkpoint Proteinsmentioning
confidence: 99%
“…Upregulation of programmed cell death-ligand 1 (PD-L1) on cancer cells inhibits immune attack via binding to its receptor, programmed cell death protein 1 (PD1), expressed on activated T cells (47). High PD-L1 expression levels have been observed on malignant plasma cells making it a promising target for immune checkpoint inhibitors (ICIs) (18,48,49). In addition, enhanced numbers of PD1 positive and T cell immunoglobulin and mucin domaincontaining protein 3 (TIM3) positive T cells were detected in the BM of MM patients suggesting reduced T cell activation (T cell exhaustion) and an immunosuppressive environment (50).…”
Section: Tumor Infiltrating Lymphocytesmentioning
confidence: 99%
“…By determining these histone modifications, different chromatin states of region can be defined[ 107 ]. Histone modifications can be subjected to tightening or loose packaging under pathological conditions, including, cancer[ 108 , 109 ]. Histones are modified by specific enzymes.…”
Section: Epigenetic Regulation Of Cscs and Cancer Cellsmentioning
confidence: 99%